ChemInform Abstract: Photoredox Catalysts: Synthesis of the Bipyrazine Ligand. Issue 26 (June 2015) - Graaf, Matthew D.; Moeller, Kevin D.
Abstract Optimum reaction conditions are studied for the synthesis of bipyrazine (II), which can be used as a photoredox catalyst.